“Digital Storytelling and Podcasts: The Islamic Studies Project as an Innovative Model for Language Education in the Digital Age” - Arya Bagus Nur Ajiyanto; Hasna; Ilham (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
The development of digital technology has brought significant changes to language learning strategies, including the integration of creative media such as digital storytelling and podcasts. The Islamic Studies Project is an initiative that utilizes both media to teach language while introducing Islamic history and culture in a contextual manner. This study aims to examine how the Islamic Studies Project developed an innovative language learning model based on Islamic history content packaged through digital and audiovisual narratives. This research approach used a qualitative case study method with data collection techniques such as video and podcast content analysis, in-depth interviews with the creative team, and observation of audience interactions on social media platforms. The results showed that the integration of digital storytelling and podcasts can increase participants' vocabulary, deepen their understanding of the cultural context, and encourage active audience engagement in the learning process. The success of this model lies in its ability to combine communicative language, engaging visuals and audio, and historical narratives relevant to the needs of the digital generation. Furthermore, the Islamic Studies Project serves as a medium for preserving cultural heritage through the documentation of local narratives and Islamic history presented in a creative format. These findings suggest that the combination of digital storytelling and podcasts has the potential to be an effective alternative approach to language education in the digital era and can be replicated in other language learning contexts with content tailored to local cultural characteristics.